Raba izraza oči so gledale v delih Ivana Cankarja - Šolak, Zdravko (Slavistična revija, 2020)
Sentences containing the compact phrase oči so gledale 'the eyes were looking', as well as phrases in which these three words are separated by some others, were isolated in works by Ivan Cankar and included in a set of 329 examples that served as a basis for research. Such phrases were used by Cankar in describing both male and female characters in various circumstances. The occurrences of such phrases in his works, their distribution in novels, as well as their length were examined quantitatively. The classification of a set of isolated examples was performed with regard to the use of adverbs with the verb gledati 'to look'.
Keywords: besedilne analize; Cankar, Ivan; dolžina povedi; pripovedna tehnika; slovenska književnost; slovenska proza